International Student Teaching: A Transformational Experience - González-Carriedo, Ricardo; López de Nava, Jesús; Salas Martínez, Manuel (Journal of International Students, 2018)
Today, being a teacher requires understanding and positively responding to the cultural and linguistic nuances present in the classroom. The increasingly diverse schools are placing higher expectations on teachers in regard to the use of multicultural practices. This is compelling teacher preparation programs to find new formulas to adequately train teacher candidates. International student teaching programs have been shown to yield important benefits for participants. This article describe an international student teacher exchange program between the University of North Texas and the University of Seville (Spain) and reflects on the effects of the experience on a Spanish preservice teacher and his mentor teacher in Texas. Implications and suggestions for teaching preparation programs are also provided.